7 - Ambiguous Transitions: Mediating Citizenship Among Youths in Cameroon: 10.4314/ad.v28i1.22173 - Fokwang, Jude (Africa Development, 2002)
This paper examines the subject of youth transition and its relationship to strug gles for citizenship in contemporary Cameroon. It is premised on the assump tion that the end of youth transition is not simply adulthood but precisely, full social and political citizenship, and that for many young people today this end is elusive. Against this background, young people have begun to redefine their identities and aspirations in relation to the state, thus questioning local mean ings of citizenship and success. The paper contends that while several studies have explored youths' differential responses to Cameroon's economic and po litical crises, none of them have accounted sufficiently for the different bio graphic trajectories mapped out by these young people. By means of case stud ies and ethnographic detail the dynamics of youth politics and the ambiguities of youth transition are analysed in relation to the wider political landscape in Cameroon. Jude Fokwang, University of Toronto, Canada